2014
DOI: 10.1111/hel.12160
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Helicobacter pylori Infection

Abstract: Helicobacter pylori relies on multiple colonization and virulence factors to persist in the human stomach for life. In addition, these factors can be modulated and vary to suit the ever-changing environment within the host individual. This article outlines the novel developments in this field of research during the past year, highlighting the cag pathogenicity island, VacA, c-glutamyl-transpeptidase as well as including recent advances in protein structure, bacteria-host interaction, and the role of stomach mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…(iv) A double intoxication then occurs, justifying numerous extradigestive pathologies described in Table 2. (v) This statement is in perfect harmony with recent literature which reports more and more extra-digestive pathologies linked to Helicobacter pylori [23,28,[35][36][37][38][39][40][41].…”
Section: Drc Helicobacter Pylori Phenomenonsupporting
confidence: 84%
“…(iv) A double intoxication then occurs, justifying numerous extradigestive pathologies described in Table 2. (v) This statement is in perfect harmony with recent literature which reports more and more extra-digestive pathologies linked to Helicobacter pylori [23,28,[35][36][37][38][39][40][41].…”
Section: Drc Helicobacter Pylori Phenomenonsupporting
confidence: 84%
“…Because H. pylori associated gastric damage is progressive the ultimate effect of eradication depends on the degree of irreversible damage [1, 5-7]. …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Microbial, host and environmental factors have been associated with the diverse clinical outcomes associated with H. pylori infection. 3 It has been shown that polymorphisms in genes of the inflammatory response, such as the pro-inflammatory cytokines IL-1b and TNF-a, increase the risk for gastric cancer in some populations but not in others.…”
Section: Introductionmentioning
confidence: 99%